Aktivitas IgY dan IgG Antitetanus setelah Perlakuan pada Berbagai pH, Suhu dan Enzim Proteolitik - Suartini, I Gusti Ayu Agung; Teguh Wibawan, I Wayan; Suhartono, Maggy T.; -, Supar; Suarta, I Nyoman (Jurnal Veteriner; Vol 8 No 4 (2007), 2007)
A study was carried out to find out an alternative method of producing antitetanus antibody (IgY) in chicken and to evaluate its activity at different levels of pH, temperatures and proteolytic enzymes. Antitetanus IgY was produced by immunization of chickens with tetanus toxoid, three times weekly at gradual doses of 100, 200, and 300 Lf, respectively. Serum samples were collected 4 weeks following the last immunization. IgY was purified by ammonium sulfat precipitation and gel filtration chromatography (Sephadex G. 120).The purified IgY was then treated at different levels of temperatures and pH as well as proteolytic enzymes. Commercial antitetanus IgG was used as control. The activities of treated IgY and IgG were tested by enzyme linked immunosorbent assay (ELISA). IgY and IgG activities were significantly reduced at 80ºC and completely destroyed at 90ºC. Treatment with pepsin significantly reduced IgY and IgG whereas trypsin slightly reduced IgY activities and has no effect on IgG activities. IgY and IgG activities were reduced significantly at pH < 3 and and only sightly reduced at pH>10. It is evident that heating at >90oC, pH at <3 and treatment with pepsin significantly reduced IgY activities and it appears that IgG was more resistent to the efect of temperatures, pH and proteolytic enzymes
Keywords: IgY, IgG, antibodies, activities, pH, heat, enzyme, ELISA